Determination of reference values of acetyl and butyryl cholinesterase activities in Serbian healthy population - Zlatković, Milica; Krstić, Nadežda; Subota, Vesna; Bošković, Bogdan; Vučinić, Slavica (Vojnosanitetski pregled, 2017)
Background/Aim. Acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) are important biomarkers of exposure to organophosphorus and carbamate insecticides. Since the estimation of the level of cholinesterase inhibition depends on the normal values which may vary in different populations, it is important to determine them in our population, which so far has not been done. Therefore, the aim of this study was to determine the reference values for AChE and BuChE in a healthy population of adults in the Republic of Serbia. Methods. The AChE activity was measured by spectrophotometry (λ = 412 nm), using a modified Ellman’s method. BuChE activity was determined by the integrated chemical system (Dimension RxLMax) with ready-made reagent cartridge for analysis. The examinees were healthy voluntary blood donors from the Institute of Transfusiology and Hemobiology, Military Medical Academy in Belgrade, Serbia. Statistical Package for Social Sciences (SPSS) software program was used for data processing. Results. In the group of 851 persons, there were 728 males and 123 females. The mean age was 39.1 ± 11.6 years. For all of them, erythrocyte AChE activity was done while BuChE was determined in 205 persons (169 males and 36 females). Their mean value of acetylcholinesterase activity was 8,090.6 ± 1,976.7 IU/L, and of butyrylcholinesterase activity was 14,556.6 ± 4,078.1 U/L. Due to lack of normal data distribution in male group (both enzymes), reference ranges were estimated as 2.5 and 97.5 percentiles. Conclusion. The results of this pilot study on cholinesterase in healthy population in the Republic of Serbia which has now been done for the first time, indicate the need for considering their wider ranges of when estimating the severity of poisoning. However, further study for BuChE with the inclusion of a larger number of females and data for body weight of the examinees, in order to get more precise reference limits, is suggested.